Integrating generative AI into Society 5.0: A paradigm for sustainable education - Sherly Deasy Anjuwita Gultom; Toetik Koesbardiati; Imam Yuadi (Research and Development in Education (RaDEn), 2025)
In the era of Society 5.0, the integration of generative technologies such as artificial intelligence (AI) into the education system is very important to achieve sustainable learning outcomes. This educational paradigm aims to harness the potential of AI in creating a learning environment that is adaptive and responsive to the needs of individual students. By using generative technology, educators can develop more interactive and personalized teaching materials, and provide faster and more accurate feedback. Qualitative research methods will be used to gain an in-depth understanding of the experiences, perceptions, and challenges faced by educators and learners in this integration process. The subjects of the study will consist of: 1). Educators who use AI technology in teaching. 2). Students involved in AI-based learning. 3). Educational institution managers who implement policies related to the use of generative technology. The research will be conducted at SMA Gloria, one of them, and several educational institutions that have implemented AI technology in their curriculum, both at elementary, middle, and high levels. Data collection techniques using semi-structured interviews will be carried out with educators and students to explore their experiences related to the use of AI technology in the teaching and learning process. In addition, the application of AI in education also allows big data analysis to understand student learning patterns and identify areas that require more attention. With the results of this approach, it is hoped that the learning process will not only be more efficient but also more inclusive, so that all students can reach their maximum potential. Thus, the integration of generative technologies in education will contribute to the achievement of the goals of Society 5.0 which focuses on human well-being and sustainability.